Real-time driver activity detection using advanced deep learning models - Md. AL Emran; Md. Ariful Islam; Md. Obaydullahn Khan; Md. Jewel Rana; Saida Tasnim Adrita; Md. Ashik Ahmed; Mahmoud M. A. Eid; Ahmed Nabih Zaki Rashed (Cognitive Neurodynamics, 2026)

Predicting hydrodesulfurization reactivity of middle distillates for producing ultra-low-sulfur diesel - Xiaoliang Ma; Hamza Albazzaz; Muhieddine A. Safa; Ahmed M. Al-Otaibi; Narjes Ghaloum; Rashed Bouresli; Shibu Jose; Ashraf M. Kamel (Fuel, 2026)

Ziziphus spina-christi as a natural feed supplement for sustainable livestock nutrition: An updated narrative review - Youssef A. Attia; Asmaa F. Khafaga; Ayman E. Taha; Islam M. Youssef; Khalid A. Asiry; Adel D. Al-Qurashi; Omer H.M. Ibrahim; Khaled H. El-Kholy; Rashed A. Alhotan; Salem R. Alyileili; Sara H.M. Hassab; Mohamed A. Al-Banoby; et al. (Livestock Science, 2026)

Effectiveness of PRF alone versus PRF plus biphasic calcium phosphate as a scaffold for gingival mesenchymal stem cells in induced vertical alveolar ridge defects - Aya Hussien; Ashraf M. Abu-Seida; Hala Abuel-Ela; Laila Rashed; Khaled Abdel-Ghaffar (Cell and Tissue Banking, 2026)

Morphogenesis of perithecia and rosette-like ascospores in Sordaria sclerogenia reveals virulence-associated metabolites and ultrastructural mechanisms of root invasion in lemon - Safaa A.M. Yousef; Motrih Al-Mutiry; Wael F. Shehata; Enas A. Almanzalawi; Tahani M. Alqahtani; Samiyah S. Al-Zahrani; Sarah Al-Rashed; Yasser S. Mostafa; Saad A. Alamri; Mohamed A. Abou-Zeid (Physiological and Molecular Plant Pathology, 2026)

Canagliflozin attenuates Parkinson’s disease and is associated with modulation of gut-inflammasome–brain axis in rats - Nada K. Gamal; Rafik Fakhry; Youmna Hatem; Engy Rashed; Reem Marzouk; Ahmed K. M. Bukr; Kerolos Safwat; Mohamed Mamdouh; Ahmed AbdElFatah; Abdelrahman Atallah; Heba Attia; Iriny M. Ayoub; et al. (Inflammopharmacology, 2026)
Recent evidence links gut dysbiosis and the gut-brain axis to the pathophysiology of Parkinson’s disease (PD), which is considered one of the most common neurodegenerative illnesses and is characterized by motor symptoms and a gradual loss of nigral dopaminergic neurons. Canagliflozin (CANA), a sodium–glucose cotransporter-2 inhibitor with emerging anti-inflammatory and antioxidant properties, has recently gained attention for its neuroprotective effects beyond glycemic control. This research aimed to examine the neuroprotective potential of CANA in a rat model of PD, focusing on its potential effect on the gut-inflammasome–brain axis. Rats were treated with rotenone (ROT) (2 mg/kg, subcutaneous) and/or CANA (20 mg/kg, oral) for 30 consecutive days. Behavioral assessment ( n = 13), biochemical assays ( n = 6), and histological and immunohistochemical analysis ( n = 3) were performed. Microbiome profiling ( n = 3) using 16S rRNA amplicon sequencing was conducted using three pooled fecal samples/group, with each pool prepared from fecal material collected from three rats and fecal metabolomic profiling ( n = 5) was performed to assess microbial metabolites. ROT intoxication caused significant motor impairments, including decreased locomotor activity, poor coordination, and increased catalepsy. Further histological examination demonstrated dopaminergic neuronal loss and α-synuclein aggregation in the substantia nigra and striatum. CANA treatment enhanced motor function, conserved neuronal integrity, and decreased α-synuclein accumulation. Moreover, ROT altered the gut microbiota with selective taxonomic shifts, including enriched abundance of Parabacteroides and Ruminococcaceae with depleted Prevotella -related taxa, in addition to fecal metabolite profile alteration. Consequently, it increased colonic oxidative stress and weakened tight junctions, all of which enhanced LPS translocation. This systemic endotoxemia generated oxidative stress, dyslipidemia, and NF-κB/NLRP3 inflammasome activation. Conversely, CANA restored gut microbial balance and their metabolites, and gut integrity, decreased LPS leakage, and reduced systemic and central oxidative stress and inflammation, preventing inflammasome activation and α-synuclein aggregation. Collectively, these findings suggest that CANA may exert neuroprotective effects in ROT-induced PD associated with modulating the gut-inflammasome–brain axis.

Corrigendum to “Numerical investigation of flare gas combustion in ethylene cracking furnaces”. [Fuel 381 (2025) 133381] - Rashed Al-ajmi; Mohammed Al-Shaghdari; Abdellatif M. Sadeq; Samer F. Ahmed; Abdulrahman S. Almutari (Fuel, 2026)

Comparative modeling of laboratory-scale biological and real industrial desulfurization processes using artificial neural networks and response surface methodology: Toward clean fuels and sustainable bioenergy - Saja Mohsen Alardhi; Sura Jasem Mohammed Breig; Ali Dawood Salman; Israa Abass Rashed; Mustafa Adnan; Fadhil Ayoob Kareem; Malik M. Mohammed (Biomass and Bioenergy, 2026)

Participatory Co-Design for Human–Elephant Coexistence: Integrating Local Knowledge into Early Warning System Planning in Odisha - Balu M. Menon; Tarek Rashed; Lekshmi Venkitesh P; Vasundharan Nidhi; Rao R. Bhavani (Environmental Management, 2026)

A review on gut microbiota and migraine severity: a complex relationship - Noha M. Gamil; Rana M. Ghorab; Reham Z. Elsadawy; Nada M. Khadrawy; Mohamed Abdelhamid; Khalid A. Ismael; Omar A. Mohamed; Mohamed M. Ata; Habiba T. Jalal; Joumana E. Zeidan; Reem T. Rashed; Riham A. El-Shiekh (Inflammopharmacology, 2026)
The gut-brain axis plays a vital role in migraine pathophysiology. Studies highlight reciprocal interactions between the central nervous system and the gastrointestinal tract. Previous research suggests that factors such as gut microbiota profiles, inflammatory mediators, neuropeptides, serotonin pathways, stress hormones, and nutritional substances influence this interaction. The pathophysiology of migraine has been linked to changes in the gut-brain axis, which affects migraine severity and frequency. Additionally, dietary approaches, including the ketogenic diet, vitamin D supplementation, omega-3 intake, probiotics, and weight loss plans, have shown promising effects in reducing migraine symptoms by positively impacting the gut microbiota and the gut-brain axis. Understanding these connections could lead to novel therapeutic strategies for effectively managing migraines. It is worth noting that research highlights several innovative treatments for migraine, such as Zelirex and Cevimide, implantable devices like Cefaly and Revilion, and new effective routes of administration for Sumatriptan. Finally, patients’ perspectives and concerns were thoroughly discussed, with a focus on future directions in the migraine-gut axis research.

Retraction notice to “Visible-light-driven photodegradation of organic pollutants by simply exfoliated kaolinite nanolayers with enhanced activity and recyclability” [Environ. Res. Volume 214, Part 3, November 2022, 113960] - Sabrin M. Abdo; Soliman I. El-Hout; Ahmed Shawky; Mohamed Nageeb Rashed; Said M. El-Sheikh (Environmental Research, 2025)

The role of visfatin and omentin-1 gene polymorphism in pancreatic ductal adenocarcinoma (PDAC) - Eman AE Badr; Waheed M. Salem; Yostena Mekhail; Hager Mohamed Rashed (Molecular Biology Reports, 2025)

The possible role of hsa_circ_0049356 and hsa-miR-338-3p in systemic lupus erythematosus disease - Mai Samir; Rana Mohamed Abd el-rahman; Laila Rashed; Mohamed Magdy; Doaa M. Gharib (Molecular Biology Reports, 2025)

Molecular docking and differential rbcl gene expression reveal variation in glyphosate herbicide tolerance of sugarcane varieties - Kawthr S. M. Allam; M. Magdy; A. M. Abd El-Aal; Nasr S. Khalil; M. A. Rashed; A. H. Atta; Reham I. AbdelHamid (Molecular Biology Reports, 2025)

Correction: The potential liver injury induced by metronidazole-provoked disturbance of gut microbiota: modulatory effect of turmeric supplementation - Abdulaziz Q. Ali; Deema Kamal Sabir; Amal F. Dawood; Mohammed Abu-Rashed; Abdulrahman Hasari; Faiz Gharqan; Salem Alnefaie; Lama E. Mohiddin; Maya M. Tatry; Dana A. Albadan; Mohanad M. Alyami; Mohammed F. Almutairi; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

The Effects of a Novel Supplement Containing Probiotics and Vitamin D as an Adjutant Therapy on sNFL and Th Cell Profiles in Patients with Multiple Sclerosis: A Randomized, Double-Blind, Placebo-Controlled Trial - Alireza Zali; Saba Sadeghi Rashed; Seyedeh Nikan Nejat; Nahid Beladi Moghadam; Javad Arasteh; Saba Taheri; Mehri Salari; Amir M Mortazavian; Mehran Ghaffari; Maryam Tajabadi Ebrahimi (Journal of Pharmaceutical Innovation, 2025)

Zonisamide nanodiamonds for brain targeting: A comprehensive study utilising in silico, in vitro, in vivo, and molecular investigation for successful nose-to-brain delivery for epilepsy management - Nihal Mohamed Elmahdy Elsayyad; Omar A. Elkady; Mohamed M. Swidan; Hassan M. Rashed; Tamer M. Sakr; Amr M. Abdelhamid; Mai A. Zaafan; Hanan M. El-Laithy (Drug Delivery and Translational Research, 2025)
The blood–brain barrier (BBB) is a stringent barrier that restricts the successful brain delivery of polar neurotherapeutics molecules. One such molecule is Zonisamide (ZNS), a hydrophilic centrally acting anti-epileptic drug. This study aims to overcome the poor ZNS BBB permeability using the nose-to-brain (NTB) carbon-based biocompatible nanodiamonds (ND) delivery system to deliver ZNS directly to the brain, bypassing the BBB, thereby enhancing its efficacy and reducing systemic side effects associated with oral ZNS currently available formulation in clinical practice. Intranasal (IN) ND-ZNS formulations were optimised using an Artificial neuronal network (ANN) and assessed for particle size (PS), zeta potential, loading efficiency (%LE), morphology, and in vitro release. The optimum radiolabelled ND-ZNS complex F1 biodistribution in different organs and its pharmacokinetics were compared to oral and IN-free ZNS in mice. Temporal lobe epilepsy (TLE) model in rats was used to compare the anti-epileptic activity of IN ND-ZNS F1 to IN free ZNS by assessing brain activity, epileptic biomarkers such as (brain neuronal specific enolase (NSE), neurofilament light polypeptide (NEFL), and matrix metallopeptidase-9 (MMP-9)), hippocampal histopathology and the modulatory effect on epigenetic miR-199/SIRT-1 and PVT-1/BDNF pathways. Optimized ND-ZNS complex F1 consists of a ZNS:ND ratio of 1:2 and sonicated for 5 min exhibited the least PS (193.7 ± 19.3 nm), adequate %LE (87.1 ± 9.2%) similar to ANN predictions, with a biphasic in vitro release profile of ZNS, beneficial for both acute and chronic epilepsy treatment. The IN delivery of ND-ZNS complex F1 showed preferential higher in vivo brain uptake with minimal systemic exposure linked with higher brain/blood ratio and significant ( p ≤ 0.05) overall enhanced pharmacokinetics expressed by C max and AUC (0-120min) when compared to oral and IN free ZNS . Moreover, the TLE model confirmed the improved anti-epileptic activity of F1 compared to IN-free ZNS regarding brain activity and hippocampal histopathology, significant suppression of serum NSE, NEFL, MMP-9 levels, miR-199/SIRT-1 pathway, and normalization of PVT-1/BDNF pathway. Therefore, ND used in this study could be a novel, promising carrier to target ZNS directly to the brain via the IN route for effective epilepsy management with less drug dosing and the least systemic side effects. Graphical Abstract

Numerical analysis of combustion characteristics and emissions of recycled flare gas in ethylene cracking furnaces - TurkiM. AL-Amoodi; Rashed Al-ajmi; Abdellatif M. Sadeq; Mohammed Al-Shaghdari; Samer F. Ahmed (Journal of Cleaner Production, 2025)

Numerical investigation of the potential of using hydrogen as an alternative fuel in an industrial burner - Rashed Al-ajmi; Abdulhafiz H. Qazak; Abdellatif M. Sadeq; Mohammed Al-Shaghdari; Samer F. Ahmed; Ahmad K. Sleiti (Fuel, 2025)

Optimizing encapsulation of garlic and cinnamon essential oils in silver nanoparticles for enhanced antifungal activity against Botrytis cinerea pathogenic disease - Nahla Alsayd Bouqellah; Awatif M. Abdulmajeed; Fawiziah Khalaf Rashed Alharbi; Ehab Mattar; Faisal Al-Sarraj; Ahmed M. Abdulfattah; Mohamed M. Hassan; Alaa Baazeem; Helal F. Al-Harthi; Arafa Musa; Tahani A.Y. Asseri; Mona H. Soliman (Physiological and Molecular Plant Pathology, 2025)

Numerical investigation of flare gas combustion in ethylene cracking furnaces - Rashed Al-ajmi; Mohammed Al-Shaghdari; Abdellatif M. Sadeq; Samer F. Ahmed; Abdulrahman S. Almutari (Fuel, 2025)

Molecular mechanisms of extracellular-ATP-mediated colorectal cancer progression: Implication of purinergic receptors-mediated nucleocytoplasmic shuttling of HuR - Abdel-Aziz S. Shatat; Elsayed M. Mahgoup; Mohammed H. Rashed; Ibrahim G. Saleh; El-Sayed Akool (Purinergic Signalling, 2024)
One of the leading causes of cancer-related deaths worldwide is colorectal cancer (CRC). Extracellular ATP (e-ATP) and purinergic receptors (P2R) play a central role in CRC proliferation and progression. Human antigen R (HuR) is becoming more and more understood to be essential for the expression of genes linked to cancer. The current study demonstrates that ATP can mediate CRC (Caco-2 cells) progression via induction of HuR nucleocytoplasmic shuttling and subsequent expression of cancer-related genes, a consequence mostly mediated via the P2R receptor. It was also noted that suppression of HuR activity by using dihydrotanshinone I (DHTS) prevents cancer-related gene expression and subsequent CRC (Caco-2 cells) progression induced by ATP. The expression of cyclin A2/cyclin-dependent kinase 2 (CDK2), Bcl-2, ProT-α, hypoxia‐inducible factor1-α (HIF1-α), vascular endothelial growth factor A (VEGF-A), transforming growth factor-β (TGF-β) and matrix metallopeptidase 9 (MMP-9) induced by ATP were highly reduced in the presence of either PPADS (non-selective P2R antagonist) or DHTS. In addition, e-ATP-induced Caco-2 cell proliferation as well as cell survival were highly reduced in the presence of either PPADS or DHTS or selective CDK-2 inhibitor (Roscovitine) or selective Bcl-2 inhibitor (ABT-263). Furthermore, it was found that MMP-9 is critical for Caco-2 cells migration induced by e-ATP as demonstrated by a clear reduction in cells migration in the presence of a selective MMP-9 inhibitor (Marimastat). Collectively, these data demonstrate that ATP through P2R activation can induce HuR nucleocytoplasmic shuttling that could be translated into an increase in cancer-related genes expression and subsequent, cell proliferation and progression.

The potential liver injury induced by metronidazole-provoked disturbance of gut microbiota: modulatory effect of turmeric supplementation - Abdulaziz Qaid Ali; Deema Kamal Sabir; Amal F. Dawood; Mohammed Abu-Rashed; Abdulrahman Hasari; Faiz Gharqan; Salem Alnefaie; Lama E. Mohiddin; Maya M. Tatry; Dana A. Albadan; Mohanad M. Alyami; Mohammed F. Almutairi; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Sensitivity analysis of cumulus parameterization scheme and data sources to simulate thunderstorms over Bangladesh using WRF model - M. Mozammel Hoque; Md. Salah Uddin Afsar; Mohammad Rashed Iqbal Faruque; S. Jamal Ahmed; A.T.M. Kaosar Jamil; M.A.K. Mallik; S.M. Quamrul Hassan (Advances in Space Research, 2024)

Enhancing the nutritional values of egg yolks of laying hens by different dietary sources of omega-3 fatty acids, vitamin e and trace elements - Youssef Attia; Ahmed A.Al Sagan; El-Sayed O.S. Hussein; Marai J. Olal; Tarek A. Ebeid; Abdulaziz A. Alabdullatif; Rashed A. Alhotan; Mohammed M. Qaid; Vincenzo Tufarelli; Gianluca Pugliese; Khaild A. Asiry; Sameer A. Nagadi; et al. (Livestock Science, 2024)

Optical Based Surface Plasmon Resonance Sensor for the Detection of the Various Kind of Cancerous Cell - Shah Ali Rafi; Wahiduzzaman Emon; Ahmed Afif Rafsan; Russel Reza Mahmud; Md. Faysal Nayan; Mahmoud M. A. Eid; Ahmed Nabih Zaki Rashed (Cell Biochemistry and Biophysics, 2024)

Ecological impacts and management strategies of pesticide pollution on aquatic life and human beings - Synan F. AbuQamar; Mohamed T. El-Saadony; Samar S. Alkafaas; Mohamed I. Elsalahaty; Sara S. Elkafas; Betty T. Mathew; Amal N. Aljasmi; Hajar S. Alhammadi; Heba M. Salem; Taia A. Abd El-Mageed; Rashed A. Zaghloul; Walid F.A. Mosa; et al. (Marine Pollution Bulletin, 2024)

Development and Enhancement of PCF-based Sensors for Terahertz-frequency Region Breast Cancer Cell Detection - A. H. M. Iftekharul Ferdous; Laxmi Rani; Md. Safiul Islam; Khalid Sifulla Noor; Sourav Roy; Mahmoud M. A. Eid; Ahmed Nabih Zaki Rashed (Cell Biochemistry and Biophysics, 2024)

Innovative Refractive Index Sensor Utilizing Terahertz Spectrum for Early Cancer Detection: a Photonic Crystal Fiber Approach - A. H. M. Iftekharul Ferdous; Md Naimur Rahman Naim; Khalid Sifulla Noor; Diponkar Kundu; Ahmed Nabih Zaki Rashed (Cell Biochemistry and Biophysics, 2024)

Ameliorative Effects of Zinc Oxide, in Either Conventional or Nanoformulation, Against Bisphenol A Toxicity on Reproductive Performance, Oxidative Status, Gene Expression and Histopathology in Adult Male Rats - Dina M. M. H. El-Kossi; Shawky S. Ibrahim; Kamel M. A. Hassanin; Nashwa Hamad; Noha A. Rashed; Ahmed Abdel-Wahab (Biological Trace Element Research, 2024)
Bisphenol A (BPA) is a widely used endocrine disruptor that represents a significant risk to male reproductive function. Zinc (Zn) is vital for appropriate development of testes and to guarantee optimal testicular function and spermatogenesis. Our goal was to investigate if zinc oxide (ZnO), either in conventional or nanoformulation, could safeguard adult male rats’ reproductive performance against the damaging effects of BPA. Signaling expression of CYP11A1 and Nrf-2 in the testis, testicular oxidant-antioxidant status, Bax/Bcl-2 apoptotic ratio, and histological examination of various reproductive organs were all evaluated. Twenty-eight adult male albino rats were divided randomly into 4 groups (7 animals each) including the control, BPA, conventional zinc oxide (cZnO) + BPA, and zinc oxide nanoparticles (ZnO-NPs) + BPA groups. The study was extended for 2 successive months. Our findings revealed strong negative effects of BPA on sperm cell characteristics such as sperm motility, viability, concentration and abnormalities. Additionally, BPA reduced serum levels of testosterone, triiodothyronine (T3), and thyroxine (T4). Also, it evoked marked oxidative stress in the testes; elevating malondialdehyde (MDA) and reducing total antioxidant capacity (TAC). BPA significantly downregulated testicular mRNA relative expression levels of CYP11A1 and Nrf-2 , compared to control. Testicular apoptosis was also prompted by increasing Bax/ Bcl-2 ratio in testicular tissue. Histopathological findings in the testes, epididymis, prostate gland, and seminal vesicle confirmed the detrimental effects of BPA. Interestingly, cZnO and ZnO-NPs significantly alleviated all negative effects of BPA, but ZnO-NPs performed better. In conclusion, our findings point to ZnO, specifically ZnO-NPs, as a viable treatment for BPA-induced testicular dysfunction.

Effect of dietary electrolyte balance and arginine to lysine ratio on hematological, antioxidant and immunological traits in dual-purpose breeding hens under cyclic heat stress condition - Youssef A. Attia; Ahmed A. Abdallah; Fulvia Bovera; Abd El-Hamid E. Abd El-Hamid; Asmaa Sh El-Naggar; Rashed A. Alhotan; Vincenzo Tufarelli; Reda M. Zaki (Journal of Thermal Biology, 2024)

New bithiophene derivative attenuated Alzheimer’s disease induced by aluminum in a rat model via antioxidant activity and restoration of neuronal and synaptic transmission - Kholoud AbdEl-Raouf; Hussein S.H. Farrag; Rashed Rashed; Mohamed A. Ismail; Monir A. El-Ganzuri; Wael M. El-Sayed (Journal of Trace Elements in Medicine and Biology, 2024)

Cuticular chemical compounds of puparial cases of three forensically important blow flies from Egypt: potential for accurate identification and forensic investigations - Eman E. Zaher; Salwa S. Rashed; Fatma A. Abdel-Halim; Samar M. Mohammed; Abeer M. Salem (International Journal of Tropical Insect Science, 2024)
The distinct and species-specific chemical compounds found on the insect cuticle have demonstrated effectiveness in various applications, including species identification. Accurate identification of fly species becomes challenging when only damaged empty puparial cases are available, making it difficult to use traditional morphological and molecular identification methods. This study aimed to analyze the chemical compositions of puparial exuviae from three forensically and medically important fly species; Lucilia sericata , Chrysomya albiceps , and Chrysomya marginalis . Gas chromatography/mass spectrometry (GC–MS) was employed to assess the chemical profiles of these exuviae and evaluate their accuracy in identifying Dipteran insects. The study revealed the presence of twelve classes of chemical compounds across the three species, with retention times ranging from 18.78 to 35.03. A total of forty-two compounds with chain lengths ranging from C12 to C45 were identified. The profiles of Ch. albiceps and L. sericata displayed similarities, with alcohol being the most abundant compound (28.6%) in L. sericata . However, alkanes, including n-alkanes, branched alkanes, and cycloalkanes, constituted the main components of the cuticles in the three species, with Ch. marginalis displaying the highest percentage. These findings represent an initial step towards utilizing hydrocarbon composition as a practical tool for distinguishing between forensic species in Egypt.

Protective influence of supplementary betaine against heat stress by regulating intestinal oxidative status and microbiota composition in broiler chickens - Ali R. Al Sulaiman; Ala M. Abudabos; Rashed A. Alhotan (International Journal of Biometeorology, 2024)

CIMCA: Infusing computational intelligence in multi-criteria analysis to assess groundwater potential for recharge - Rashed Uz Zzaman; Muhammad Ali Nayeem; Sara Nowreen; Imran Hossain Newton; AKM Saiful Islam; Anwar Zahid; M. Sohel Rahman (Environmental Modelling & Software, 2023)

Exploiting fungi in bioremediation for cleaning-up emerging pollutants in aquatic ecosystems - Synan F. AbuQamar; Hassan I. Abd El-Fattah; Maha M. Nader; Rashed A. Zaghloul; Taia A. Abd El-Mageed; Samy Selim; Belal A. Omar; Walid F. Mosa; Ahmed M. Saad; Khaled A. El-Tarabily; Mohamed T. El-Saadony (Marine Environmental Research, 2023)

High prevalence of multidrug-resistant Campylobacter jejuni in sheep and goats milk in Jordan - Mohammad M. Obaidat; Rashed M. Alshdaifat (International Dairy Journal, 2023)

Preparation and characterization of nanomuscovite by intercalation method for adsorption of heavy metals from polluted water - M. Nageeb Rashed; A. E Arifien; F. A. El-Dowy (Environmental Geochemistry and Health, 2023)
In this study, nanomuscovite adsorbents were prepared by intercalation with various organic intercalates (DTAB-TTAB-DTPA-PA-PN) and used to remove Cd 2+ and Pb 2+ from polluted water. The best nanomuscovite was prepared using DTPA and muscovite (Muc/DTPA) and characterized by XRD, TEM, EDX, FTIR, and BET surface area. The developed nanoadsorbent was used to remove Cd 2+ and Pb 2+ from polluted water. The effect of various factors, including contact time, adsorbent dosage, solution pH, and temperature, was investigated. The results reveal that the maximum adsorption of Cd 2+ and Pb 2+ was 91.5% and 97%, respectively, at the initial metal concentration 50 ppm, adsorbent dosage 0.2 g, contact time 60 min, solution temperature 25 °C, and pH 6 for Pb 2+ and pH 7 for Cd 2+ . Adsorption isotherm models (Freundlich, Langmuir, Dubunin–Radushkevich, and Temkin isotherm models) as well as kinetic models (pseudo-first-order, pseudo-second-order, Elovich, and intra-particle diffusion models) were employed to evaluate the experimental results. The adsorption of Cd 2+ and Pb 2+ on Muc/DTPA fitted well within the Langmuir isotherm model and followed pseudo-second-order kinetics. Thermodynamics parameters of metal adsorption indicated exothermic and spontaneous processes. Results were applied to the real wastewater that showed high Cd 2+ and Pb 2+ removal.

Dry-spun carbon nanotube ultrafiltration membranes tailored by anti-viral metal oxide coatings for human coronavirus 229E capture in water - Ahmed O. Rashed; Chi Huynh; Andrea Merenda; Julio Rodriguez-Andres; Lingxue Kong; Takeshi Kondo; Joselito M. Razal; Ludovic F. Dumée (Journal of Environmental Chemical Engineering, 2023)

Chemical Activation of Sludge from Drinking Water Treatment Plant for Adsorption of Methylene Blue Dye - Mohamed F. Soliman; M. Nageeb Rashed; Abeer Ali Ahmd (Water, Air, & Soil Pollution, 2023)
The objective of this study is to explore the preparation and application of sludge produced in plants of drinking water treatment, to remove methylene blue (MB) dye from polluted water. Adsorbate (methylene blue) is prepared in the lab. as a stock solution. To create new adsorbents, chemical activation of the used sludge has been carried out. The activation is performed by HCl and H 2 O 2 and a mixture of HCl and H 2 O 2 . The experiments were carried out under different boundary conditions, like the initial concentration of dye, dosage of adsorbent, solution pH, contact time, and temperature of the adsorption, to determine the optimum boundary conditions for operation. All of the experiments in this study were carried out in a batch system. The results show that sludge activation by a mixture of 2:1 HCl/ H 2 O 2 was selected as the best chemically activated adsorbent (removal of 99.9%). For the best MB adsorption results, the following criteria must be met: 50 ppm initial dye concentration, 90 min of contact time, pH 7, and a dosage of 0.25 g of the adsorbent. Adsorbents suit the Langmuir and Freundlich models well, according to applications of the Freundlich Isotherm and Langmuir models.

Characterization and phylogenetic analysis of the complete mitochondrial genome of Mango tilapia (Sarotherodon galilaeus: Cichlidae) - Yosur G. Fiteha; M. A. Rashed; R. A. M. Ali; M. Magdy (Molecular Biology Reports, 2023)
Background Sarotherodon galilaeus (Linné, 1758) is a member of the family Cichlidae, which is considered the most important aquaculture freshwater species endemic to Africa and the Middle East. The genetics and molecular biology of this species are rare. This requires more comprehensive mitochondrial genomes-based phylogenetics to enhance understanding of the relationship and delineate this species. Methods and results Here, we assembled the complete mitogenome of S. galilaeus using Illumina high-throughput sequencing technology. The mango tilapia mitogenome was 16,631 bp in length with an AT composition of 53.4% and 46.4% GC content. It encodes 37 genes comprising two ribosomal RNA genes (rRNAs), 22 transfer RNA genes (tRNAs), and 13 protein-coding genes (PCGs) as well as the D-loop known as the control region. The phylogenetic tree was conducted to provide a relationship within the haplotilapiine lineage based on the maximum likelihood method, and the newly sequenced S. galilaeus was clustered with other Sarotherodon species. Conclusion Our results provide a new perception of the genetic basis of S . galilaeus species for further research on systematics, evolution, population genetics, and molecular ecology.

An eco-sustainable approach towards heavy metals remediation by mangroves from the coastal environment: A critical review - Krishna Kumar Yadav; Neha Gupta; Shiv Prasad; Lal Chand Malav; Javed Khan Bhutto; Akil Ahmad; Amel Gacem; Byong-Hun Jeon; Ahmed M. Fallatah; Basim H. Asghar; Marina M.S. Cabral-Pinto; Nasser S. Awwad; et al. (Marine Pollution Bulletin, 2023)

Electrocatalytic ultrafiltration membrane reactors designed from dry-spun self-standing carbon nanotube sheets - Ahmed O. Rashed; Chi Huynh; Andrea Merenda; Si Qin; Maxime Maghe; Lingxue Kong; Takeshi Kondo; Joselito M. Razal; Ludovic F. Dumée (Chemical Engineering Journal, 2023)

Estimation of the piled embankment critical height: a systematic review - Nooran Mohamed Edries; Mohamed Ezzat Al-Atroush; Ahmed Rashed; Sayed M. Ahmed (Innovative Infrastructure Solutions, 2023)

Mesenchymal Stem Cells and Selenium Nanoparticles Synergize with Low Dose of Gamma Radiation to Suppress Mammary Gland Carcinogenesis via Regulation of Tumor Microenvironment - Omayma A. R. Abozaid; Laila A. Rashed; Sawsan M. El-Sonbaty; Amira I. Abu-Elftouh; Esraa S. A. Ahmed (Biological Trace Element Research, 2023)
Breast cancer is one of the most prevalent and deadliest cancers among women in the world because of its aggressive behavior and inadequate response to conventional therapies. Mesenchymal stem cells (MSCs) combined with green nanomaterials could be an efficient tool in cell cancer therapy. This study examined the curative effects of bone marrow–derived mesenchymal stem cells (BM-MSCs) with selenium nanoparticles (SeNPs) coated with fermented soymilk and a low dose of gamma radiation (LDR) in DMBA-induced mammary gland carcinoma in female rats. DMBA-induced mammary gland carcinoma as marked by an elevation of mRNA level of cancer promoter genes (Serpin and MIF, LOX-1, and COL1A1) and serum level of VEGF, TNF-α, TGF-β, CA15-3, and caspase-3 with the reduction in mRNA level of suppressor gene (FST and ADRP). These deleterious effects were hampered after treatment with BM-MSCs (1 × 10 6 cells/rat) once and daily administration of SeNPs (20 mg/kg body weight) and exposure once to (0.25 Gy) LDR. Finally, MSCs, SeNPs, and LDR notably modulated the expression of multiple tumor promoters and suppressor genes playing a role in breast cancer induction and suppression.

Assessment of radiometric hazards in the Southern Industrial Zone, Jeddah City, using car-borne gamma-ray spectrometry system - Hussein M. Harbi; Helmy S. Abuenaga; Mohamed A. Rashed; Ali H. Atef (Arabian Journal of Geosciences, 2022)

Four new phenolics and antiparasitic secondary metabolites from Flacourtia rukam Zoll. & Mortizi - Naglaa I. Afifi; Abeer S. Moawad; Mohamed A. Zaki; Mostafa E. Rateb; Mohammed H. Rashed; Ibrahim G. Saleh; Mona H. Hetta; Rabab M. Mohammed (Natural Product Research, 2022)

Climate change vulnerability in Bangladesh based on trend analysis of some extreme temperature indices - Istiak Ahmed; Sheikh Ishtiaque; Taslima Zahan; Md. Saif Uddin Rashed; Ranjit Sen; Md. Faruque Hossain; Shyamal Brahma; Imrul Mosaddek Ahmed; M. Akhtar Hossain; Mohammad Akkas Ali; Abu Hena Sorwar Jahan; Sheikh Imtiaz; et al. (Theoretical and Applied Climatology, 2022)

Ag nanoparticle-decorated chitosan/SrSnO3 nanocomposite for ultrafast elimination of antibiotic linezolid and methylene blue - M. Faisal; Md Abu Rashed; Jahir Ahmed; Mabkhoot Alsaiari; Mohammed Jalalah; Saeed A. Alsareii; Farid A. Harraz (Environmental Science and Pollution Research, 2022)

Potential aptitude of four olive cultivars as anticancer and antioxidant agents: oleuropein content - Shimaa A. Rashed; Tamannouha I. Saad; Salama M. El-Darier (Rendiconti Lincei. Scienze Fisiche e Naturali, 2022)
Olea europaea L. (olive, Oleaceae) constitutes a source of many bioactive compounds, which have recognized benefits for both human health and technological purposes. The present article was carried out to evaluate the biological activity of oleuropein (an ester of 2-(3,4-dihydroxyphenyl) ethanol (hydroxytyrosol) which has the oleosidic skeleton that is common to the secoiridoid glucosides of Oleaceae). It occurred in leaf extracts of the four olive cultivars (Chemlali, Manzanilla, Picaul and Toffahi) as a source for some anticancer and antioxidant agents and their consequences on the action of Hordeum vulgare (barley). The total phenolic and flavonoid compounds were extracted from olive leaves by ethanol 95% then analyzed by high-performance liquid chromatography (HPLC). The study evaluates the anticancer activity of the ethanolic extract of olive leaves against breast and hepatocellular carcinoma cells showing high values. Also, the extract exhibited highly consequence on the antioxidant potentiality of barley which was assessed using the diphenyl picryl hydrazyl method (DDPH). These results pave the way for utilization of olive leaves as a source of natural anticancer and antioxidant agents.

Cytotoxic and anti-diabetic potential, metabolic profiling and insilico studies of Syzygium cumini (L.) Skeels belonging to family Myrtaceae - Seham Salah Eldin Elhawary; Amira kamal Eldin Elmotayam; Doaa kamel Alsayed; Eman Maher Zahran; Merivat Ahmed Fouad; Amany Ameen Sleem; Hanan Elimam; Mohamed H. Rashed; Alaa M. Hayallah; Anber F. Mohammed; Usama Ramadan Abdelmohsen (Natural Product Research, 2022)

A Machine Learning-based Approach for Groundwater Mapping - Rashed Uz Zzaman; Sara Nowreen; Irtesam Mahmud Khan; Md. Rajibul Islam; Nabil Ibtehaz; M. Saifur Rahman; Anwar Zahid; Dilruba Farzana; Afroza Sharmin; M. Sohel Rahman (Natural Resources Research, 2022)

Antimicrobial and synergistic effect of Moroccan native Argania spinosa essential oil for modulating of antibiotics resistance - Ahmed Nafis; Lahcen Hassani; Najat Marraiki; Sarah Al-Rashed; Abdallah M. Elgorban; Asad Syed; Marcello Iriti (Natural Product Research, 2021)

Evolutionary computing of the compression index of fine-grained soils - Saif Alzabeebee; Younis M. Alshkane; Kamal Ahmad Rashed (Arabian Journal of Geosciences, 2021)

A Roadmap for Policy-Relevant Sea-Level Rise Research in the United Arab Emirates - Hannah Melville-Rea; Clare Eayrs; Nasser Anwahi; John A. Burt; Denise Holland; Fatin Samara; Francesco Paparella; Ahmed Hassan Al Murshidi; Maryam Rashed Al-Shehhi; David M. Holland (Frontiers in Marine Science, 2021)
The United Arab Emirates (UAE) has a long-term policy horizon, the financial capital, and a vision for a sustainable knowledge-based economy. These characteristics uniquely situate it as a potential leader for sea-level rise research. Climate science is already growing, and at the center of the UAE's pivot toward climate research is a burgeoning concern for sea-level rise. Over 85% of the UAE's population and more than 90% of the nation's infrastructure is within a few meters of present-day sea-level. With its low-lying and shallow-sloping geography (about 35 cm per km), this high-value coastline, including the rapidly expanding cities of Dubai and Abu Dhabi, is particularly vulnerable to sea-level rise. Meanwhile, limited regional research and data scarcity create deep uncertainty for sea-level projections. We set out a potential roadmap for the UAE to capitalize on its strengths to create usable and relevant sea-level projections for the region. With a newly established Climate Change Research Network, the UAE government is beginning to draw together universities and research centers for “furthering effective data collection and management, and advancing policy-relevant research on climate impacts and adaptation 1 .” By consolidating ideas from the science community within the UAE, we identify promoters and barriers to data gathering, information sharing, science-policy communication, and funding access. Our paper proposes pathways forward for the UAE to integrate sea-level science with coastal development and form best practices that can be scaled across climate science and throughout the region.

The occurrence and dietary intake related to the presence of microplastics in drinking water in Saudi Arabia - Lama Almaiman; Alaa Aljomah; Mohammed Bineid; Futoon M. Aljeldah; Fahad Aldawsari; Bettina Liebmann; Ievgeniia Lomako; Katharina Sexlinger; Rashed Alarfaj (Environmental Monitoring and Assessment, 2021)

Treatment of hepatitis C virus infection with direct-acting antivirals plus ribavirin eliminates viral RNA from peripheral blood mononuclear cells and reduces virologic relapse in diverse hepatic parenchymal changes - Mohamed Darwish Ahmed Abd Alla; Reham M. Dawood; Hassan Abd EL-Hafeth Rashed; Galal Farrag; Islam Abdelmawla Emran Ammar; Mohamed Mahmoud Abdel-Halim Mahmoud; Ghada M. Salum; Ahmed Mohamed Abdulhamid Altanbouly; Mai A. El Meguid; Mostafa K. El Awady (Archives of Virology, 2021)

Sedimentology and basin-fill history of the Cenozoic succession of the Sylhet Trough, Bengal Basin, Bangladesh - Farida Khanam; M. Julleh Jalalur Rahman; M. Mustafa Alam; Rashed Abdullah (International Journal of Earth Sciences, 2021)

Development of potential map for groundwater abstraction in the northwest region of Bangladesh using RS-GIS-based weighted overlay analysis and water-table-fluctuation technique - Sara Nowreen; Imran Hossain Newton; Rashed Uz Zzaman; A. K. M. Saiful Islam; G. M. Tarekul Islam; Md. Saiful Alam (Environmental Monitoring and Assessment, 2021)

Repurposing of Secukinumab as Neuroprotective in Cuprizone-Induced Multiple Sclerosis Experimental Model via Inhibition of Oxidative, Inflammatory, and Neurodegenerative Signaling - Amany El-Shahawy Abdel-Maged; Amany M. Gad; Laila Ahmed Rashed; Samar S. Azab; Eman A. Mohamed; Azza S. Awad (Molecular Neurobiology, 2020)

Unconfined Compressive Strength (UCS) and Compressibility Indices Predictions from Dynamic Cone Penetrometer Index (DCP) for Cohesive Soil in Kurdistan Region/Iraq - Younis M. Alshkane; Kamal Ahmad Rashed; Hyam Saleh Daoud (Geotechnical and Geological Engineering, 2020)

Highly effective surface modification using plasma technologies toward green coloration of polyester fabrics - Fatma Abdelghaffar; Rehab A. Abdelghaffar; Usama M. Rashed; Hend M. Ahmed (Environmental Science and Pollution Research, 2020)

Imaging contamination surrounding a wastewater dumpsite using 2 terrain conductivity meters - Mohamed A. Rashed; Hussein M. Harbi; Burhan A. Niyazi; Ali H. Atef (Arabian Journal of Geosciences, 2020)

TP53 genetic polymorphisms and susceptibility to cervical cancer in Bangladeshi women: a case–control study - Mohd Nazmul Hasan Apu; A. Z. M. Rashed; Tafsir Bashar; Md Morshadur Rahman; Md Shaki Mostaid (Molecular Biology Reports, 2020)

Isolation, identification and characterization of endophytic bacteria antagonistic to Phytophthora palmivora causing black pod of cocoa in Malaysia - Wael Alsultan; Ganesan Vadamalai; Ahmad Khairulmazmi; Halimi Mohd Saud; Abdullah M. Al-Sadi; Osamah Rashed; Ahmad Kamil Mohd Jaaffar; Abbas Nasehi (European Journal of Plant Pathology, 2019)

MicroRNA as a prognostic biomarker for survival in childhood acute lymphoblastic leukemia: a systematic review - Wafaa M. Rashed; Mahmoud M. Hamza; Marwa Matboli; Sherin I. Salem (Cancer and Metastasis Reviews, 2019)

Pediatric diffuse intrinsic pontine glioma: where do we stand? - Wafaa M. Rashed; Eslam Maher; Mohamed Adel; Ossama Saber; Mohamed Saad Zaghloul (Cancer and Metastasis Reviews, 2019)

Rutin inhibits carfilzomib-induced oxidative stress and inflammation via the NOS-mediated NF-κB signaling pathway - Naif O. Al-Harbi; Faisal Imam; Mohammed M. Al-Harbi; Othman A. Al-Shabanah; Moureq Rashed Alotaibi; Homood M. As Sobeai; Muhammad Afzal; Imran Kazmi; Ammar Cherkess Al Rikabi (Inflammopharmacology, 2019)

Preparation and Characterization of Biomass Carbon–Based Solid Acid Catalysts for the Esterification of Marine Algae for Biodiesel Production - Azeem Rana; Mohammed S. M. Alghazal; Mohammed M. Alsaeedi; Rashed S. Bakdash; Chanbasha Basheer; Abdulaziz A. Al-Saadi (BioEnergy Research, 2019)

Spatiotemporal trends in freshwater availability in the Red Sea Hills, Saudi Arabia - Burhan A. Niyazi; Mohamed Ahmed; Jalal M. Basahi; Milad Z. Masoud; Mohamed A. Rashed (Arabian Journal of Geosciences, 2018)

Characterizing Zebra Chip Symptom Severity and Identifying Spectral Signatures Associated with ‘Candidatus Liberibacter solanacearum’-Infected Potato Tubers - Zhiguo Zhao; Sean M. Prager; Regina K. Cruzado; Xi Liang; William R. Cooper; Gongshe Hu; Arash Rashed (American Journal of Potato Research, 2018)

Effects of Holding Temperatures on the Development of Zebra Chip Symptoms, ‘Candidatus Liberibacter Solanacearum’ Titers, and Phenolic Levels in ‘Red La Soda’ and ‘Russet Norkotah’ Tubers - C. M. Wallis; A. Rashed; F. Workneh; L. Paetzold; C. M. Rush (American Journal of Potato Research, 2017)

Sugar beet wireworm Limonius californicus damage to wheat and barley: evaluations of plant damage with respect to soil media, seeding depth, and diatomaceous earth application - Arash Rashed; Christopher W. Rogers; Mahnaz Rashidi; Juliet M. Marshall (Arthropod-Plant Interactions, 2017)

Experimental assessment of non-edible candlenut biodiesel and its blend characteristics as diesel engine fuel - H. K. Imdadul; N. W. M. Zulkifli; H. H. Masjuki; M. A. Kalam; M. Kamruzzaman; M. M. Rashed; H. K. Rashedul; Azham Alwi (Environmental Science and Pollution Research, 2017)

First Record of Porpita porpita (Cnidaria: Hydrozoa) from the coral reef ecosystem, Bangladesh - M. Shah Nawaz Chowdhury; S. M. Sharifuzzaman; Sayedur Rahman Chowdhury; Md. Rashed-Un-Nabi; M. Shahadat Hossain (Ocean Science Journal, 2016)

Adsorptive removal of Cu(II) and Pb(II) onto mixed-waste activated carbon: kinetic, thermodynamic, and competitive studies and application to real wastewater samples - Zeid Abdullah ALOthman; Mohamed Abdelaty Habila; Nora H. Al-Shalan; Sulaiman M. Alfadul; Rahmat Ali; Ibrahim Gar Al alm Rashed; Bader Alfarhan (Arabian Journal of Geosciences, 2016)

Diabetes-induced changes in the morphology and nociceptinergic innervation of the rat uterus - Saeed Tariq; Syed M. Nurulain; Hameed Rashed; Mohamed Lotfy; Starling Bright Emerald; Surya Koturan; Kornélia Tekes; Ernest Adeghate (Journal of Molecular Histology, 2016)

Conjugate Heat Transfer in an Annulus with Porous Medium Fixed Between Solids - Irfan Anjum Badruddin; Salman Ahmed N. J.; Abdullah A. A. A. Al-Rashed; N. Nik-Ghazali; Mohammed Jameel; Sarfaraz Kamangar; H. M. T. Khaleed; T. M. Yunus Khan (Transport in Porous Media, 2015)

Petrology, geochemistry and remote sensing data of island arc assemblage along Wadi Abu Marawat, Central Eastern Desert, Egypt - A. M. Asran; R. Kh. Bekir; E. Abdel Rahman; A. Abdel El-Rashed (Arabian Journal of Geosciences, 2013)

Effect of recombinant erythropoietin on ischemia–reperfusion-induced apoptosis in rat liver - Heba M. Shawky; Sandra M. Younan; Leila A. Rashed; Heba Shoukry (Journal of Physiology and Biochemistry, 2012)

Analysis of Heat and Mass Transfer in a Vertical Annular Porous Cylinder Using FEM - Irfan Anjum Badruddin; N. J. Salman Ahmed; Abdullah A. A. A. Al-Rashed; Jeevan Kanesan; Sarfaraz Kamangar; H. M. T. Khaleed (Transport in Porous Media, 2012)

Temporal and spatial distribution of fish and shrimp assemblage in the Bakkhali river estuary of Bangladesh in relation to some water quality parameters - Md. Rashed-Un-Nabi; Md. Abdulla Al-Mamun; Md. Hadayet Ullah; M. Golam Mustafa (Marine Biology Research, 2011)

Effects of streptozotocin-induced long-term diabetes on parietal cell function and morphology in rats - Salim M. A. Bastaki; Ernest Adeghate; Irwin S. Chandranath; Naheed Amir; Saeed Tariq; Rashed S. Hameed; Abdu Adem (Molecular and Cellular Biochemistry, 2010)

Screening for tetracycline residues in food products of animal origin in the State of Kuwait using Charm II radio-immunoassay and LC/MS/MS methods - Hani M. Al-Mazeedi; Alaa B. Abbas; Hussam F. Alomirah; Wafaa Y. Al-Jouhar; Siham A. Al-Mufty; Mohamed M. Ezzelregal; Rashed A. Al-Owaish (Food Additives & Contaminants: Part A, 2010)

Gastroprotective and antisecretory effects of Ailanthus excelsa (Roxb) - Larissa S. Melanchauski; Ana Paula G. S. Broto; Thiago M. Moraes; Ana Lúcia M. Nasser; Ataa Said; Usama W. Hawas; Khaled Rashed; Wagner Vilegas; Clélia A. Hiruma-Lima (Journal of Natural Medicines, 2010)

Fruit Stones from Industrial Waste for the Removal of Lead Ions from Polluted Water - M. N. Rashed (Environmental Monitoring and Assessment, 2006)

Animal Hair as Biological Indicator for Heavy Metal Pollution in Urban and Rural Areas - M. Nageeb Rashed; M. E. Soltan (Environmental Monitoring and Assessment, 2005)

Multiple dolomitization events of the Lower Carboniferous Um Bogma Formation, west central Sinai, Egypt - M. N. Shaaban; H. M. Holail; K. N. Sedeik; M. A. Rashed (Carbonates and Evaporites, 2005)

Cadmium and Lead Levels in Fish (Tilapia Nilotica) Tissues as Biological Indicator for Lake Water Pollution - M. N. Rashed (Environmental Monitoring and Assessment, 2001)

Water Resources in the GCC Countries: An Overview - Muhammad F. Al-Rashed; Mohsen M. Sherif (Water Resources Management, 2000)

Dolomitization of middle miocene buildups, Um Gheig area, Red Sea coast, Egypt - Mohamed N. Shaaban; Hanafy M. Holail; Mohamed A. Rashed (Carbonates and Evaporites, 1997)

Distribution and chemical fractionation of some heavy metals in bottom sediments of Lake Nasser - S. M. N. Moalla; R. M. Awadallah; M. N. Rashed; M. E. Soltan (Hydrobiologia, 1997)